The Academic Triad: Procrastination, Self-Discipline and Anxiety in University Life - Salaam, Shahrukh; Mustafa, Sana; Fatima (Annals of Human and Social Sciences, 2024)
This study aims to examine the relationship between procrastination, self-discipline, and anxiety among university students and explore their impact on academic and mental health. Students’ academic performance and mental health are highly influenced by my psychological factors including procrastination, self-discipline, and anxiety. In this quantitative study a correlational research design was employed with non-probability purposive sampling. Data were collected from (N=200) university students using the Procrastination Assessment Scale (PAS), Self-Control Scale (SCS), and State-Trait Anxiety Inventory (STAI). Procrastination showed a positive correlation with anxiety, while self-discipline exhibited a negative correlation with both procrastination and anxiety symptoms. Self-discipline was a significant negative predictor of anxiety. By Integrating qualitative methods alongside quantitative measures could provide deeper insights into the experiences and perceptions of university students regarding the study variables. Consequently by implementing targeted interventions to enhance self-discipline and reduce procrastination, universities can support students in managing anxiety symptoms and improving overall well-being